Improving Sex Education Awareness of Students of Madrasah Ibtidaiyah Setia Budi Tamiajeng Trawas Mojokerto through Service-Learning Approach: A Community Service - Salis Khoiriyati; Widi Astuti; Eka Rizki Amalia (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Sex education should be given from an early age to prevent sexual harassment. Giving sex education to children is an effort to provide information about the function of the private parts. It makes them aware of sex and sexuality and the importance of taking them as privacy. It is also an opportunity to instill moral values and ethics. This community service employed a Service-Learning approach by utilizing adapted learning methods as well as adequate facilitators. In this program, sex education is given to grade 1 (as an early introduction) and grade 6 students (as they are approaching pre-puberty) at a primary school with material related to everyday life. This program ran for two weeks and received a satisfying response from the students and the school stakeholders. The result shows that the students understood the material very well. In addition, there is a reasonably positive behavior change in the students' awareness to take care of themselves in association with their classmates, especially those related to their private parts.